Attributions for Atheism: Perceptions that Atheism is a Choice are Associated with Prejudice against Atheists among Christians, but Not Jews or Nonbelievers. Issue 2 (3rd April 2021) - Moss, Aaron J.; Fitzpatrick, James; O'Brien, Laurie T.
ABSTRACT: Is believing that atheism is a choice related to prejudice against atheists? The present research draws on attributional models of prejudice to examine the relationship between perceptions that atheism is a choice and anti-atheist prejudice among Christians, Jews, and nonbelievers. We hypothesized that Christians would be more likely than Jews (Sample 1 and 3) and nonbelievers (Samples 1, 2, and 3) to believe atheism is a choice. Further, we hypothesized that the relationship between perceptions of choice and anti-atheist prejudice would be stronger among Christians than Jews and nonbelievers. In three samples of college students and U.S. adults (N = 859), Christians were more likely than others to believe atheism is a choice and perceptions of choice uniquely predicted Christians' prejudice toward atheists. By examining perceptions of choice, our research reveals a novel source of anti-atheist prejudice, but a source with deep roots in the psychology of prejudice.